Intellectual Capital and Firm’s Operational Efficiency - Putri, Nuventin Asna; Suryani, Ani Wilujeng (The Indonesian Journal of Accounting Research, 2025)
This research aims to determine the effect of intellectual capital (IC) on operational efficiency in 180 companies in the basic materials, consumer cyclicals, consumer non-cyclicals, healthcare, and industrials subsectors listed on the Indonesia Stock Exchange from 2015 to 2024. IC is measured using the Modified Value-Added Intellectual Coefficient (MVAIC) and operational efficiency, as determined by Data Envelopment Analysis (DEA). Generalized Least Squares regression analysis is used to test the hypothesis, which shows that human capital has a positive effect on operational efficiency. This means that superior employee knowledge and skills can provide creative ideas for changing or developing the company's production system. In contrast, relational capital has a negative effect. However, innovation capital and process capital have no effect. Previous studies have only analyzed the influence of IC, consisting of human capital and structural capital components, on operational efficiency. This study incorporated relational capital, innovation capital, and process capital components to expand the scope of IC in relation to company performance.